The Effectiveness of Posters and Videos About Prevention of Dengue Hemorrhagic Fever (DHF) on Community Knowledge and Attitudes in The Working Area of Paal V Puskesmas Jambi - Jonathan Disyon Manurung; Puspita Sari; Usi Lanita; M. Ridwan; Vinna Rahayu Ningsih (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: The Ministry of Health reported that in 2022 there were approximately 143,000 cases of dengue fever in Indonesia. According to data from the Jambi Provincial Health Profile in 2022, there were 1,381 cases of DHF, which caused 9 deaths, based on data from the Jambi City Health Office, the highest number of DHF cases in Jambi City in 2022 was 36 cases at the Paal V Health Center. The Paal V Health Center has made efforts to eradicate DHF, but cases still appear high, this is influenced by several factors such as knowledge and attitudes. The purpose of this study was to determine the effectiveness of posters and videos on dengue prevention on the knowledge and attitudes of the community in the working area of Puskesmas Paal V, Jambi City. Methods: Quantitative research design with an experimental approach. Total samples of 30 poster media and 30 video media were selected using accidental sampling technique. The variables in this study are poster media, videos, knowledge and attitudes. Data collection using questionnaires and data processing in the form of bivariate and univariate analysis. The test used in this study is the Wilcoxon test if the data is not normally distributed and the paired t-test if the data is normally distributed. Results: There is an effect of posters and videos on knowledge with a p-value of poster media (p-value=0.001) and video media (p-value=0.001). There is an effect of poster and video media on attitude with a p-value of poster media (p-value=0.049) and video media (p-value=0.041). Conclusion: Based on the results of the research that has been done, video media is more effective than poster media on knowledge and attitudes about the prevention of dengue hemorrhagic fever (DHF). Therefore, in order to use video media as a medium in conducting counseling about dengue hemorrhagic fever (DHF).